Dexmedetomidine as an Anesthetic Adjuvant in Patients Undergoing Transsphenoidal Resection of Pituitary Tumor. Issue 3 (July 2015) - Gopalakrishna, Kadarapura N.; Dash, Prasanta K.; Chatterjee, Nilay; Easwer, Hariharan V.; Ganesamoorthi, Arimanickam
Abstract : Background: Transnasal transsphenoidal (TNTS) resection of pituitary tumors involves wide fluctuation in hemodynamic parameter and causes hypertension and tachycardia due to intense noxious stimuli during various stages of surgery. None of routinely used anesthetic agents effectively blunts the undesirable hemodynamic responses, and therefore usually there is a need to use increased doses of anesthetic agents. Dexmedetomidine (DEX) an α-2 adrenergic receptor agonist, because its sympatholytic and antinociceptive properties may ensure optimal intraoperative hemodynamic stability during critical moments of surgical manipulation. In addition, DEX reduced the anesthetic requirement with rapid recovery at the end of surgery. The main aim of our study was to evaluate the effect of DEX on perioperative hemodynamics, anesthetic requirements, and recovery characteristics in patients undergoing TNTS resection of pituitary tumors. Materials and Methods: Forty-six patients scheduled for elective TNTS resection of pituitary tumor were randomized to receive a continuous infusion of DEX (group D) or 0.9% saline (group C). Patients in both the groups were subjected to a standardized anesthesia comprising of induction with propofol, fentanyl, vecuronium, and positive pressure ventilation with O2 /air (1:1)/isoflurane. The response entropy target range during maintenance of anesthesia was 40 to 60. The hemodynamic variables at various stages of surgery, intraoperative anesthetic, and analgesic and recovery characteristics were recorded. Results: Total fentanyl consumption during the study period was significantly lower in group D compared with group C (4.7 and 7.7 µg/kg, respectively; P <0.01). End-tidal isoflurane concentration requirement was found to be significantly reduced in group D compared with group C throughout the surgical period. Fentanyl and end-tidal isoflurane concentration requirement was reduced in group D compared with group C by 40% and 33.3%, respectively. Heart rate and mean arterial pressure were significantly higher in the group C compared with group D after intubation, during various stages of surgery and immediately after extubation. The group D had excellent surgical conditions and lesser bleeding in comparison to group C. Emergence time and extubation time were significantly shorter in group D compared with group C. Conclusions: DEX as an anesthetic adjuvant improved hemodynamic stability and decreased anesthetic requirements in patients undergoing TNTS resection of pituitary tumor. In addition, DEX provided better surgical field exposure conditions and early recovery from anesthesia.